Make (dis)believe: creative spectacularization of the war on theatre stage in The Great Evil - Petrikas, Martynas (Creativity Studies, 2025)
This article deals with the issue of production of belief on stage of the theatre. The research presented in the article aims to contribute to the discussion on how understanding tools and techniques of building fiction in theatre helps to deconstruct and understand mediatized images of reality. The case in point is a Lithuanian theatre production The Great Evil (orig. Didis blogis, 2015, director Árpád Schilling), which will be analyzed as an example of militarized conflict depicted as a spectacle. Analysis of the performance and of its reception using tools proposed by Erving Goffman allowed to find aesthetic means specific to the theatre that were used to present the spectacularization and artifice as weapons of modern warfare.